ANALISIS KARAKTERISTIK GAMBAR PADA ANAK SLOW LEARNER DI KELAS III SEKOLAH DASAR - femmy rosefani, - (2020)
Drawing is a fun activity. Drawing activities are important aspects in expressing children's feelings. Slow learner children are not able to express what they feel directly, and therefore through their pictures, expressions and desires are visible. In reality drawing activities carried out on slow learners are still exemplified by the teacher and given patterns, so that slow learners are less able to express what they want to draw. Therefore, an analysis is needed to determine the characteristics of the images of slow learners to find out the expressions that they pour through the pictures. The purpose of this study are 1) to determine the characteristics of the images made by slow learners in grade III elementary school; 2) the process of drawing activities takes a long time, removes a lot of objects, and the results of the drawing are not completed; 3) find out the benefits of drawing activities for slow learners in grade III primary school. This study uses a case study research method with slow learner children's research subjects. Based on research conducted shows that 1) the characteristics of images made by slow learners have significant differences from images of normal children; 2) the process of drawing activities takes quite a longer time, a lot of deleting objects, and the results of the drawing do not finish; 3) the advantages of drawing activities morecommunicative in telling pictures that are made and able to draw according to their thoughts and imagination without being exemplified or given a pattern. Keywords: analysis, picture characteristics, slow leraner children